Investigating cognitive transfer within the framework of music practice: genetic pleiotropy rather than causality - Mosing, Miriam A.; Madison, Guy; Pedersen, Nancy L.; Ullén, Fredrik (Developmental science, 2016)
The idea of far transfer effects in the cognitive sciences has received much attention in recent years. One domain where far transfer effects have frequently been reported is music education, with the prevailing idea that music practice entails an increase in cognitive ability (IQ). While cross‐sectional studies consistently find significant associations between music practice and IQ, randomized controlled trials, however, report mixed results. An alternative to the hypothesis of cognitive transfer effects is that some underlying factors, such as shared genes, influence practice behaviour and IQ causing associations on the phenotypic level. Here we explored the hypothesis of far transfer within the framework of music practice. A co‐twin control design combined with classical twin‐modelling based on a sample of more than 10,500 twins was used to explore causal associations between music practice and IQ as well as underlying genetic and environmental influences. As expected, phenotypic associations were moderate (r = 0.11 and r = 0.10 for males and females, respectively). However, the relationship disappeared when controlling for genetic and shared environmental influences using the co‐twin control method, indicating that a highly practiced twin did not have higher IQ than the untrained co‐twin. In line with that finding, the relationship between practice and IQ was mostly due to shared genetic influences. Findings strongly suggest that associations between music practice and IQ in the general population are non‐causal in nature. The implications of the present findings for research on plasticity, modularity, and transfer are discussed. We examined cognitive transfer within the framework of music practice using a genetically informative sample. We showed that when controlling for genetic influences the association between practice and IQ disappeared, suggesting no causal association between music practice and IQ. Our findings suggest that associations between training and cognitive abilities do not necessarily reflect far transfer, but rather suggest preexisting differences influence both training and cognitive ability.